Eksistensi Pembagian Harta Waris Adat Lampung Pepadun Secara Sistem Patrilineal Pada Lampung Timur - Yapiter Marpi (Fakultas Hukum, Universitas Muhammadiyah Pontianak, 2022)
The customary inheritance law differs along with the differences in the kinship system used in each tribe. The inheritance of the indigenous people of Lampung Pepadun is in the form of inheritance by the majority of men, because the Lampung Pepadun tribe tends to a patrilineal kinship system, the eldest son becomes the sole heir to replace his father. The legal consequences that then arise with the occurrence of death are about the management and continuation of the rights and obligations of both the person who died and the relatives left behind. In the Indonesian context, it is necessary to have legal conceptions and principles derived from customary law to formulate a national law in order to meet the legal needs of the Indonesian people. This type of research is a field research using a qualitative approach with inductive data analysis. The result of this research is the system applied in the distribution of inheritance rights to the eldest child in the Lampung Pepadun indigenous community. The law of parental or bilateral inheritance is to provide equal rights between male heirs and female heirs, both to husbands and wives, as well as boys and girls, including male and female families.